2005
DOI: 10.1021/jf050222m
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Stilbenes in Hop Pellets from Different Cultivars

Abstract: About 30% of the polyphenols in wort and beer derive from hop, but little is yet known about their nutritional impact. The recent discovery of trans-resveratrol and piceid isomers in hop opens new doors to understanding beer health benefits. In the present work, resveratrol was quantified by HPLC-APCI-MS/MS in pellets from 9 different cultivars. Concentrations ranging from 4 to 9 mg/kg trans-piceid, from 2 to 6 mg/kg cis-piceid, and up to 1 mg/kg trans-resveratrol were detected. As previously shown for total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 22 publications
3
48
2
1
Order By: Relevance
“…grape juice and fortified wine or other sources suggested to contain resveratrol, such as hops, which are present in beer [35], or cherries [36]. Nevertheless, our estimation of resveratrol intake might be acknowledged as sensitive on a population level, as the sources that were not used contain a low concentration of resveratrol [27,35,36] and/or are not widely consumed in the total population.…”
Section: Discussionmentioning
confidence: 99%
“…grape juice and fortified wine or other sources suggested to contain resveratrol, such as hops, which are present in beer [35], or cherries [36]. Nevertheless, our estimation of resveratrol intake might be acknowledged as sensitive on a population level, as the sources that were not used contain a low concentration of resveratrol [27,35,36] and/or are not widely consumed in the total population.…”
Section: Discussionmentioning
confidence: 99%
“…Stilbenes in hops and beer Jerkovic et al (2005) analysed nine varieties of hops (Humulus lupulus) and identified trans-and cis-piceid and trans-resveratrol in all varieties. None of the varieties contained cis-resveratrol.…”
Section: 34mentioning
confidence: 99%
“…Flavonoidy analyzoval pomocí metody HPLC s UV detekcí (De Cooman et al, 1998). Jerkovic et al (2005) analyzoval koncentraci stilbenů ze skupiny polyfenolů (cis-a trans-resveratrol a cis-a trans-piceid) v peletách devíti odrůd chmele pomocí metody HPLC a detekcí MS s chemickou ionizací za atmosférického tlaku (APCI). Z výsledků srovnání celkové koncentrace stilbenů a alfa-kyselin vyplývá, že čím menší koncentraci alfa-kyselin odrůda obsahuje, tím je větší obsah stilbenů.…”
Section: Metody Pro Ověřování Autenticity Odrůd Chmele -účInný Nástrounclassified
“…Using HPLC and MS detection with chemical ionization at atmospheric pressure (APCI), Jerkovic et al (2005) analyzed the concentration of stilbenes from the group of polyphenols (cis-and transresveratrol and cis-and trans-piceid) in pellets of nine hop varieties. The comparison of the total concentration stilbenes and alpha-acids showed that the lower the concentration of alpha-acids in the variety, the higher the content of stilbenes.…”
Section: Polyphenolsmentioning
confidence: 99%